Modeling and simulation of biomass drying in vortex chambers. (17th February 2015) - Eliaers, Philippe; Ranjan Pati, Jnyana; Dutta, Subhajit; De Wilde, Juray
Abstract: High-G fluidization in vortex chambers allows intensifying the drying of granular materials. The modeling, simulation and scale-up of vortex chamber based biomass dryers are addressed. Non-stationary experiments, batch for the biomass, are carried out to complement the data on continuous woody biomass drying in vortex chambers available in the literature. The drying models differ in the way they do or do not account for interfacial mass and heat transfer limitations, a non-uniform distribution of the moisture in the biomass particles and intra-particle diffusion limitations. Discrimination between the different proposed drying models and estimation of the model parameter(s) follows from simulations of both the continuous and batch experiments and regression. The retained biomass drying model is then used to study scale-up of the technology, focusing on continuous operation. Two major issues are addressed: (i) the product uniformity and (ii) the air consumption and utilization. Different vortex chamber configurations are simulated and analyzed: a single chamber or different chambers operated in parallel or in series (compartmented), allowing introducing a CSTR-in-series type behavior for the particles, combined with air feeding in parallel or in series over the different chambers. Highlights: Modeling of biomass drying in vortex chambers using a non-stationary technique. Significant process intensification through high-G operation confirmed. Scale-up issues studied with the developed drying model. Product uniformity can be improved by compartmenting the vortex chamber. Air utilization can be optimized by re-usage in different vortex chambers/compartments.